The impact of perceived environmental competitiveness on employee mental health: a moderated mediation model of job crafting and work–family conflict - Cheng, Sheng; Wang, Yumei (Frontiers in Public Health, 2024)
Drawing from the conservation of resources theory, this study proposes that individuals who perceive environmental competitiveness may improve their mental health through their job crafting behaviors at work. Data were collected from 450 full-time Chinese employees using a three-wave time-lagged approach. The results showed that perceived environmental competitiveness is positively correlated with job crafting, and job crafting has a positive relationship with mental health. Moreover, the results indicated that job crafting mediates the relationship between perceived environmental competitiveness and mental health. Additionally, the present study found that work-family conflict plays a moderating role in the relationships among environmental competitiveness, job crafting and mental health. A moderated mediation model was proposed in this study. Finally, theoretical and practical implications of this study are also discussed.